Understanding intrusion detection through visualization - Axelsson, Stefan; Sands, David (Kluwer Academic Publishers eBooks, 2006)
Table of contentsForeword by Dr. John McHugh, Canada Research Chair, Director, Privacy and Security Laboratory, Dalhousie University Halifax, N.S. Canada.- Preface.- Introduction.- An Introduction to Intrusion Detection.- The Base-Rate Fallacy and the Difficulty of Intrusion Detection.- Visualising Intrusions: Watching the Webserver.- Combining a Bayesian Classifier with Visualisation.- Visualising the Inner Workings of a Self Learning Classifier.- Visualisation for Intrusion Detection: Hooking the Worm.- References.- Author Index.- Index.